2022
DOI: 10.1039/d2tc01942f
|View full text |Cite
|
Sign up to set email alerts
|

Largely enhanced energy density of BOPP–OBT@CPP–BOPP sandwich-structured dielectric composites

Abstract: Biaxially oriented polypropylene (BOPP) is the most widely used polymer dielectric in film capacitor for its excellent dielectric advantages and competitive cost-performance. However, there is still an great challenge to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Each sample was measured 12 times, and the highest and lowest values of E were discarded, so n is 10 in this work. Weibull distribution was adopted to process the electric breakdown strength. , The high electric field D – E loops of the composites were measured at 10 Hz by using a TF analyzer 2000 (aixACCT, Aachen, Germany), and gold electrodes with a diameter of 2 mm were sprayed on both sides before the measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sample was measured 12 times, and the highest and lowest values of E were discarded, so n is 10 in this work. Weibull distribution was adopted to process the electric breakdown strength. , The high electric field D – E loops of the composites were measured at 10 Hz by using a TF analyzer 2000 (aixACCT, Aachen, Germany), and gold electrodes with a diameter of 2 mm were sprayed on both sides before the measurement.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, the BOPP-based sandwich-structured composite films have shown advantages of a heterostructure to enhance the energy storage properties of BOPP. , The dielectric constant of chlorinated polypropylene (CPP) is higher than that of BOPP, and it has good adhesion to BOPP. Clemens et al found that CPP integrated with isotactic PP in the heating process because the unit crystal size of CPP was similar to that of isotactic PP, so CPP is a good binder of BOPP.…”
Section: Introductionmentioning
confidence: 99%
“…17d). 381 Owing to CPP, strong interlayer adhesion was ensured with no observable defects. By doing so, the multilayers gave dielectric constants of 2.95 at 1 kHz, an improvement from 2.07 exhibited by commercial BOPP.…”
Section: Approaches To Durable Actuatorsmentioning
confidence: 99%
“…Currently, biaxially oriented polypropylene (BOPP), possessing high breakdown strength (E) and low dielectric loss (tan δ), stands as the state-of-the-art commercial dielectric film for capacitor applications. 3,4 However, the low dielectric constant (K) of polypropylene results in a limited discharged energy density (U e ), leading to an increased capacitor volume and restricting its broader applications. 5 The high U e is jointly determined by both enhanced K and E for linear dielectric, U e = 1/2Kε 0 E 2 , where ε 0 represents the vacuum permittivity (8.85 × 10 −12 F/m).…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al introduced polar BaTiO 3 into the BOPP sandwich structure, enhancing the interfacial polarization of the composite film and significantly increasing the dielectric constant. 4 In this work, a high U e and ultrahigh η polypropylene-based dielectric film was prepared comprising lanthanide functional fillers (WBG) using a melt extrusion process. The WBG has the advantages of good processing stability, high melting temperature and repeatability, and high nucleation efficiency, which induces high levels of the β crystal at low loading.…”
Section: Introductionmentioning
confidence: 99%